1995
DOI: 10.1016/s0969-2126(01)00229-5
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of a cyanogenic β-glucosidase from white clover, a family 1 glycosyl hydrolase

Abstract: Sequence comparisons between beta-glucosidases of the same family show that residues Glu183 and Glu397 are highly conserved. Both residues are positioned at the end of a pocket located at the C terminus of the barrel and have been assigned the respective roles of proton donor and nucleophile on the basis of inhibitor-binding and mutagenesis experiments. These roles are consistent with the environments of the two residues. The pocket itself is typical of a sugar-binding site as it contains a number of charged, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(186 citation statements)
references
References 40 publications
6
175
0
5
Order By: Relevance
“…The location of C170 in the model precludes participation of this cysteine residue in formation of a disulfide bridge in Zm-p60.1. Furthermore, an intramolecular disulfide bridge, formed between cysteine residues in the positions equivalent to C205 and C211, was identified in the crystal structure of CBG [7]. Finally, in plant b-glucosidases and b-thiolglucosidases with highly related amino-acid sequences, and acting as dimers, a cysteine residue in the position equivalent to the Zm-p60.1 position 205 is conserved followed by a second cysteine residue separated by 5±9 amino-acid residues (C211 in the Zm-p60.1; Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The location of C170 in the model precludes participation of this cysteine residue in formation of a disulfide bridge in Zm-p60.1. Furthermore, an intramolecular disulfide bridge, formed between cysteine residues in the positions equivalent to C205 and C211, was identified in the crystal structure of CBG [7]. Finally, in plant b-glucosidases and b-thiolglucosidases with highly related amino-acid sequences, and acting as dimers, a cysteine residue in the position equivalent to the Zm-p60.1 position 205 is conserved followed by a second cysteine residue separated by 5±9 amino-acid residues (C211 in the Zm-p60.1; Fig.…”
Section: Discussionmentioning
confidence: 98%
“…7; only monomer unit of Zm-p60.1 dimer is shown for simplicity) was constructed on the basis of the X-ray analysis of a closely related cyanogenic b-glucosidase CBG [7]. In the CBG structure, there are two cysteine residues forming a disulfide bridge in positions equivalent to C205 and C211.…”
Section: Homology Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional structures are available for a large number of Family1 enzyme, the first solved being that of the white clover (Trifolium repens) cyanogenic β-glucosidase [14]. As members of Clan GH-A they have a classical (α/β) 8 TIM barrel fold with the two key active site glutamic acids being approximately 200 residues apart in sequence and located at the C-terminal ends of β-strands 4 (acid/base) and 7 (nucleophile) [15,16].…”
Section: Three-dimensional Structures Of Gh1mentioning
confidence: 99%
“…The NEP sequence motif, of which the Glu residue is an acid/ base catalyst, was found at residues 257-259, and the sequence ITENG, of which the Glu residue is a catalytic nucleophile of β-glucosidases, was also found at residues 468-472 (Jenkins et al 1995;Keresztessy et al 1994). The residues involved in the binding of the glycone (glucose) Copyright © 2015 The Japanese Society for Plant Cell and Molecular Biology moiety are highly conserved in all GH1s (Barrett et al 1995;Rye and Withers 2000;Saino et al 2014;Sue et al 2006;Zechel and Withers 2000), and these residues were also found at Gln-108, His-212, Asn-257, Glu-258, Glu-526, and Trp-527 in the DeF26G1 sequence ( Figure 5). …”
Section: Isolation Of Full-length Def26g1 Cdnamentioning
confidence: 99%